2021
DOI: 10.1093/sleep/zsab014
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and cardiometabolic risk: a cluster analysis of actigraphy-derived sleep profiles in adults and children

Abstract: Study objectives Sleep plays an important role in cardiometabolic health. While the importance of considering sleep as a multidimensional construct is widely appreciated, studies have largely focused on individual sleep characteristics. The association between actigraphy-derived sleep profiles and cardiometabolic health in healthy adults and children has not been examined. Methods This study used actigraphy-measured sleep dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…Several studies have identified sleep patterns by comprehensively considering multiple objectively assessed sleep characteristics, including cluster analysis [10,27], latent class analysis [28,29], and composite sleep scores considering self-reported sleep behaviors [30], but only a few studies have been conducted in children and adolescents. [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have identified sleep patterns by comprehensively considering multiple objectively assessed sleep characteristics, including cluster analysis [10,27], latent class analysis [28,29], and composite sleep scores considering self-reported sleep behaviors [30], but only a few studies have been conducted in children and adolescents. [36].…”
Section: Discussionmentioning
confidence: 99%
“…Cluster analysis provides the ability to consider multidimensional sleep characteristics from a holistic perspective [9]. To date, only one study has applied this approach to identify sleep patterns and explored their relationships with cardiometabolic health in children and adults using accelerometry-measured sleep data [10]. Four patterns were identified, and the "overall good sleepers" pattern was associated with more favorable body mass index (BMI) and metabolic syndrome severity score.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep quality is diminished in patients with cardiometabolic disease [ 54 ] and intake of dietary polyphenols [ 55 ], and supplementation of Montmorency tart cherry has been demonstrated to enhance sleep quality and symptoms of insomnolence [ 56 , 57 ]. Therefore, general sleep quality will be examined using the Pittsburgh sleep quality index [ 58 ], daytime sleepiness using the Epworth Sleepiness Scale [ 59 ] and symptoms of insomnolence via the Insomnia Severity Index [ 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…Certain adverse childhood experiences such as physical, sexual, and emotional abuse and neglect have a lasting impact on sleep quality in adulthood, highlighting the need to mitigate their impact to prevent negative health outcomes associated with poor sleep quality. [15]…”
Section: Time Needed To Fall Asleepmentioning
confidence: 99%